A study of psychiatric morbidity and substance use pattern among the adolescents attending department of psychiatry of a tertiary hospital in Northeastern India - Udayan Majumder; Senjam Gojendra; Ningombam Heramani; Rajkumar Lenin Singh (Annals of Indian Psychiatry, 2019)
Context: This hospital-based study attempts to explore the morbidity load of categorized mental disorders along with the pattern of substance use in the adolescent group of people presenting to a tertiary hospital of Manipur, India. Aims: This study aims to document sociodemographic profiles, psychiatric morbidity, and substance use pattern among the adolescents attending the Department of Psychiatry of a tertiary hospital of Manipur, India. Settings and Design: This study was a cross-sectional, hospital-based study. Subjects and Methods: This cross-sectional study included 474 consecutive adolescent patients (10–19 years) attending both outpatient department and inpatient department of the Department of Psychiatry of a Tertiary Hospital of Manipur, India, were enrolled during the study. Diagnoses were made according to the ICD-10. Statistical Analysis: The statistical software, namely SPSS 22.0 and R environment ver. 3.2.2 were used for the analysis of the data. Results: Almost 68.4% were within 16–19 years, 51.3% lived with their families, 56.1% were male, 62% of them were Hindus, and majority of them were from urban background (54.4%). Neurotic, stress-related, and somatoform disorders were the highest (41.4%), followed by psychotropic substance use in 21.3%, mood disorders in 14.8%, schizophrenia and delusional disorder in 12.2%, behavioral and emotional disorder in 9.3%, and disorders of adult personality and behavior (F60-69) in 0.4%. The most common categorical psychiatric diagnosis in males due to psychotropic substance use (37.2%) while neurotic, stress-related, and somatoform disorders (61.1%) were the most common categorical diagnosis in females. Conclusions: Very few studies have been conducted to reflect the scenario and pattern of psychiatric morbidities in the state of Manipur. We hope this study will be helpful in reflecting the psychiatric morbidity load in the adolescent group for helping them with early diagnosis and intervention.